The Financial Planning and Financial Literacy of Ex-Malaysia Indonesian Migrant Workers - Brahmana, Rayenda Khresna; Brahmana, Ritzky Karina (University of Economics, Prague, 2016)
Indonesian migrant workers (IMW) face life difficulties after returning back to Indonesia. This is a contrary condition considering their contribution to their home family in Indonesia while working abroad. Literature mentions that their financial planning is the root of the poverty of ex-IMW. Therefore, this research adopts literacy theory to explain this phenomenon. This research conducted a survey among 548 ex-IMW and measures their financial literacy and financial planning. This research also maps their asset ownership to examine the relationship between financial literacy and asset ownership. Overall, this research documents that financial literacy contributes statistically significantly and positively to financial planning. Furthermore, this research shows that asset ownership is closely related to financial literacy. In a nutshell, this research concludes that it is important for migrant workers to have good knowledge of financial issues, because having good financial literacy helps the migrant workers to plan their finance and budget much better, thereby helping them to avoid the poverty trap. Therefore, policymakers such as migrant worker authorities and/or Indonesian embassies abroad have to institute financial education programmes for migrant workers before they return to Indonesia.